ESTIMASI PENGUBAH KEADAAN MELALUI PENGOLAHAN MASUKAN DAN KELUARAN - Wahjudi, Rudy S (Jurnal Teknik Elektro, 2003)
The best resulted of feedback control system design by using state variable feedback. But notall of the state variables feedbacks are available. The solution of this problem is useestimator. Through input and output measurements, then drive to estimator so can requiredoutput estimator near state variable.This paper presents the estimator design through artificial control model. So that todetermined the gain estimator and simulated using by software MALAB version 6.5. Theexperiment to carry out by three replicated of simulations with difference estimator gain.The good design will be achieved if estimator gain to caused that transient time estimatormore fast then transient time plant.Keywords: estimator, state variable, state variable feedback1. Pendahuluan